CBRNE Mobile Analytical Laboratory of the State Fire Service – Analysis of Technical and Normative Solutions Applied - Grzegorz Bugaj; Paweł Janik (Safety & Fire Technology, 2025)
Aim: This article offers a multifaceted analysis of the technical and normative aspects involved in the design, construction, and commissioning process of the Polish State Fire Service’s (PSP) mobile CBRNE analytical laboratory. Special attention is given to the technical solutions’ compliance with applicable national and international standards, as well as the laboratory’s operational effectiveness during rescue operations in environments threatened by chemical, biological, radiological, nuclear, and explosive hazards. Introduction: Mobile CBRNE laboratories are crucial for identifying and neutralizing asymmetric threats, whether originating from industrial accidents, natural disasters, or deliberate terrorist or military actions. In response to the growing complexity and unpredictability of modern threats, and the increased demand for rapid and precise emergency service response, the Polish State Fire Service has implemented an innovative technological solution. This newly developed and constructed laboratory vehicle enables advanced in situ analysis, maintaining the highest standards of biological and chemical safety. This represents a significant breakthrough in the operational capabilities of specialized units carrying out operations within the national rescue and firefighting system. Methodology: The analysis is based on a case study of the PSP’s mobile laboratory, including a review of technical, normative, and operational documentation. Particular attention was paid to compliance with PN-EN standards, ISO standards, NATO guidelines, and national legal regulations concerning mobile laboratories and biological safety. Conclusions: The analysis revealed that the PSP’s mobile laboratory meets key normative requirements while ensuring high operational effectiveness. The integration of advanced filtration systems, hermetically sealed working compartments, and specialized analytical equipment allows for comprehensive operations in diverse field conditions. The article emphasizes the importance of consistency between normative requirements and practical technical solutions in ensuring the safety and effectiveness of rescue operations. Keywords: State Fire Service, biological safety, mobile laboratory, CBRNE, analytical equipment